Génétique textuelle & écritures mono- et multilingues - Leblay C (Association canadienne de traductologie, 2022)
In this contribution, we have chosen the methodological approach of textgenetics that systematically focuses on text production processes before considering the final product. The main concepts of textgenetics (succession,immediacy, linearity) are updated and applied to new heterogeneous, collaborative, polygraphic, and professional corpora. By adopting this approach, it becomes possible to calibrate the learning of translators-writers from a procedural point of view. It is also possible to follow and visualize the transformations step by step: One can learn to reflect critically on one’s own writing, and visual resources can refine the process. Using basic textgenetics concepts, we have to consider the different ways of studying what textgenetics calls avant-texte, in order to be able to classify the main genetic corpus, from the first studied literary texts to the most recent multimodal texts, including professional (mono- and plurilingual) writings.